Az egyetemi testnevelés kialakulása és fejlődése Debrecenben a két világháború között - Király, Sándor (Gerundium, 2018)
The Formation and Development of Physical Education at the University of Debrecen Between the Two World Wars. This study offers an overview of the beginnings, formation, as well as the production of the institutional and human resources of university-level physical education. The reader is provided with information pertaining to the difficulties relating to the introduction of mandatory university-level physical education and the role Debrecen—and Debrecen’s Gymnastics Association: DTE—played in securingaccommodation for the gymnastics lessons. Thus, we can learn about the changes and shifts, from optional to obligatory, of the university physical education of female students. We can also receive information as to who the first physical education instructors at the university were and additional information concerning those university educators who were the chief supporters of the systematic exercise of students and of university-level sports. It was due to the dedication of these people that it was in Debrecen that a position for sports physician was first created. The duties of the sports physician included the health check-up of students who participated in the gymnastics exercises. In addition, the study also includes information pertaining to how the university sports centre was created and extended as well as how the interest of the student body in exercise was enhanced by the University Athletic Club of Debrecen (DEAC)